Allergic airway disease in Italian bakers and pastry makers. - De Zotti, R (1994)
A survey was carried out on respiratory symptoms and skin prick test response to common allergens (atopy), storage mites, and occupational allergens among 226 bakers and pastry makers from 105 small businesses in northern Italy. Atopy was present in 54 workers (23.4%); 40 workers (17.7%) were skin positive to at least one storage mite, 27 (11.9%) to wheat flour and 17 (7.5%) to alpha-amylase. Work related asthma was reported by 11 (4.9%) workers and rhinoconjunctivitis by 31 (17.7%); 22 workers (10.2%) complained of chronic bronchitis. The distribution of skin prick test results among bakers and among 119 white collar workers did not indicate (by logistic analysis) an increased risk for bakers to skin sensitisation to common allergens, storage mite, or to a group of five flours. Sensitisation to wheat flour, on the other hand, was present only among exposed workers. Skin sensitisation to occupational allergens was significantly associated with atopy (p < 0.001), smoking habit (p = 0.015), and work seniority (p = 0.027). The risk of work related symptoms was associated with sensitisation to wheat or alpha-amylase, and with atopy, but not with sensitisation to storage mites, work seniority, or smoking habit. The results of the study indicate that there is still a significant risk of allergic respiratory disease among Italian bakers. Not only wheat allergens, but also alpha-amylase must be considered as causative agents, although sensitisation to storage mites is not important in the occupational allergic response. Atopy must be regarded as an important predisposing factor for skin sensitisation to occupational allergens and for the onset of symptoms at work. The data confirm that for effective prevention, greater care should be taken not only in limiting environmental exposure, but also in identifying susceptible people.